Meningkatkan Keterampilan Vokasional Membuat Kokedama Melalui Pembelajaran Discovery Learning Bagi Anak Tunarungu Kelas VII di SLB Luak Nan Bungsu Kota Payakumbuh - Septriani, Yazvi (RC-INSTITUT, 2019)
This study aims to improve the vocational skills of making kokedama through discovery learning. Problems that occur in the process of learning skills at SLB Luak Nan Bungsu are children who have difficulty in making skills that will be useful for their future lives. Learning given by the teacher about kokedama is less varied andcauses the children to be less motivated in making these skills, and due to the lack of teacher knowledge about kokedama making skills. Based on these problems, this study was conducted to prove that discovery learning can improve the ability to make kokedama in deaf children. In this study, classroom action research can improve the skills of making kokedama in deaf class VII students at SLB Luak Nan Bungsu